1994
DOI: 10.1111/j.1559-1816.1994.tb00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Bystander Responses to Public Episodes of Child Abuse

Abstract: Bystander responses to public episodes of child abuse were surveyed among 269 self reported witnesses. Respondents completed an 80‐item self‐report questionnaire which inquired into a broad range of events, experiences, and behaviors surrounding naturally occurring incidents of perceived child abuse witnessed in public places. Almost one‐half of the sample reported having witnessed at least one event of child abuse in public, but only one out of four witnesses acted to intervene. Data analyses identified 40 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 43 publications
2
78
0
Order By: Relevance
“…First, the inclusion of other relevant correlates of public responses to cases of IPVAW would help to further understand the processes involved in decision making leading to different types of responses to incidents of IPVAW. The inclusion of other possible predictors of public responses to IPVAW such as the influence of emotional factors, attitudes towards family privacy, victim-blaming attitudes, trust in the authorities' effectiveness, perception of the support available to victims, or contextual effects such as neighborhood social disorder would also help to better understand public responses to incidents of IPVAW (Christy & Voigt, 1994;Gracia & Herrero, 2007;Gracia, Herrero, Lila, & Fuente, 2009;Hadeed & El-Bassel, 2006;James, Johnson, & Raghavan, 2004;Levine, 1999;Raghavan, Mennerich, Sexton, & James, 2006;Weiner, 1980). Another potential limitation is that we used hypothetical scenarios as a stimulus rather than actual situations, and it is possible that public responses might differ from what they actually would do in a real situation (Fritzsche, Finkelstein, & Penner, 2000;Robinson & Chandek, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…First, the inclusion of other relevant correlates of public responses to cases of IPVAW would help to further understand the processes involved in decision making leading to different types of responses to incidents of IPVAW. The inclusion of other possible predictors of public responses to IPVAW such as the influence of emotional factors, attitudes towards family privacy, victim-blaming attitudes, trust in the authorities' effectiveness, perception of the support available to victims, or contextual effects such as neighborhood social disorder would also help to better understand public responses to incidents of IPVAW (Christy & Voigt, 1994;Gracia & Herrero, 2007;Gracia, Herrero, Lila, & Fuente, 2009;Hadeed & El-Bassel, 2006;James, Johnson, & Raghavan, 2004;Levine, 1999;Raghavan, Mennerich, Sexton, & James, 2006;Weiner, 1980). Another potential limitation is that we used hypothetical scenarios as a stimulus rather than actual situations, and it is possible that public responses might differ from what they actually would do in a real situation (Fritzsche, Finkelstein, & Penner, 2000;Robinson & Chandek, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Batson et al (1996) found that the expectation of oneself receiving a shock affected self-reported empathy when observing a same-sex peer receive a shock, although this pattern was only observed in females. Christy and Voigt (1994) found that those who reported being abused as a child indicated that they would be more likely to intervene if they saw a child being abused than those who had never been abused.…”
Section: Past and Vicarious Experiencementioning
confidence: 99%
“…Batson et al (1996) found that for females but not males, the expectation of oneself receiving a shock affected self-reported empathy when one observed a same-sex peer receiving a shock. Christy and Voigt (1994) found that those who reported being abused as a child indicated that they would be more likely than those who had never been abused to intervene if they saw a child being abused. These studies focus on self-reported feelings and intentions rather than examining prosocial behavior per se.…”
Section: Personal Experiencementioning
confidence: 99%